Answer:
2x^2 + 6.
Step-by-step explanation:
Replace the x in f(x) by g(x):
f(g(x)) = 2(x^2 + 3)
= 2x^2 + 6.
6 times 2/3 equal to 4
Juanita ues 4 lemons to make lemonade
Q^2 - 125 = 0
q^2 = 125
q = +/- sqrt 125 = 11.18, -11.18
129,407 because 12 ten thousands is 120,000 and 8 thousands is 8,000. 14 hundreds is 1,400 and 7 ones is 7 so 120,000+8,000+1,400+7=129,407
Answer:
Step-by-step explanation:
<u>Property of the odd function is:</u>
<u>Same applies to the given function:</u>
- f(x) = -2x⁵ + x³ - 7x
- f(- x) = -2(-x)⁵ + (- x)³ - 7(-x) = 2x⁵ - x³ + 7x = - (2x⁵ + x³ - 7x) = - f(x)